Elementary characterization of Ti metal alloys used in implant dentistry (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The main goal of present work is analytical characterization of standard dental implants broadly used by Brazilian dentists. An ideal biological alloy for dental implants must have very high biocompatibility, which means that such material should not provoke any serious adverse tissue response. Dental implants are generally marketed as commercially pure titanium (TiCP) due to their excellent mechanical and physical properties. However, sometimes other alloys are employed and consequently it is essential to study the chemical elements present in those alloys that could bring prejudice for the health. Present work investigated TiCP metal alloys used for dental implant manufacturing and evaluated the presence of elements. For alloy characterization and identification of elements it was used EDXRF technique. This method allows to perform the qualitative and quantitative analysis of the materials using the spectra of the characteristic X-rays emitted by the elements present in the metal samples. The experimental setup was based on two X- ray tubes, Mini X model with Ag and Au targets and X-123SDD detector (AMPTEK) and a 0.5 mm Cu collimator, developed due to specific sample geometrical and topography characteristics. Obtained results showed that implant alloys are not exactly TiCP but were manufactured using Ti-Al-V alloy, which contained Fe, Ni, Cu and Zn. The presence of such metals as Al and V in all studied samples shows very clear that studied implants were not manufactured from TiCP alloy. Moreover, according to the American Society for Testing and Materials (ASTM), these elements should not be present in TiCP.